Analisis Hidrologi Untuk Penentuan Debit Banjir Rancangan di Bendungan Way Besai - Nivitha, Mutya; Winarno, Dwi Joko; Kusumastuti, Dyah Indriana (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2018)
AbstractResource which is often used for energy source is water as hydro power plant. One of hydro power plant in Lampung province is Way Besai Hydro Power Plant. Considering the importance of this hydro power plant for people, extreme things on the hydro power plant like flood, certainly not desirable. Hydrologic analysis required for get result that was flood design as action anticipation.This study was conducted in Way Besai watershed, Sumber Jaya, West of Lampung. The data required of this study are rainfall data from five stations, flow Way Besai data from 1986 to 2000, and daily rainfall data from two station.From frequency analysis, obtained design flood for the largest single data group return period of 2 years is return period 5 years 131,00 m3/s, return period 10 years 178,42 m3/s, return period 25 years 253,71 m3/s, return period 50 years 322,66 m3/s, return period 100 years 403,45 m3/s, and 499,81 m3/s for return period 200 years. From HEC-HMS, the flood design for return period 2 years sebesar 71,2 m3/s, return period 5 years 90,6 m3/s, return period 10 years 105,7 m3/s, return period 25 years 128,6 m3/s, return period 50 years 156,6 m3/s, return period 100 years 190,8 m3/s and 233,7 m3/s for return period 200 years. Based on calibration result used RMSE, obtained RMSE value is 3,12. Keywords: watershed, design flood, Way Besai, HEC-HMS